Uterine Natural Killer Cells: A Rising Star in Human Pregnancy Regulation - Xie, Min; Li, Yan; Meng, Yi-Zi; Xu, Peng; Yang, Yong-Guang; Dong, Shuai; He, Jin; Hu, Zheng (Frontiers in Immunology, 2022)
Uterine natural killer (uNK) cells are an immune subset located in the uterus. uNK cells have distinct tissue-specific characteristics compared to their counterparts in peripheral blood and lymphoid organs. Based on their location and the pregnancy status of the host, uNK cells are classified as endometrial NK (eNK) cells or decidua NK (dNK) cells. uNK cells are important in protecting the host from pathogen invasion and contribute to a series of physiological processes that affect successful pregnancy, including uterine spiral artery remodeling, fetal development, and immunity tolerance. Abnormal alterations in uNK cell numbers and/or impaired function may cause pregnancy complications, such as recurrent miscarriage, preeclampsia, or even infertility. In this review, we introduce recent advances in human uNK cell research under normal physiological or pathological conditions, and summarize their unique influences on the process of pregnancy complications or uterine diseases. Finally, we propose the potential clinical use of uNK cells as a novel cellular immunotherapeutic approach for reproductive disorders.